Digital Innovations for Effective Management Analysis in the Context of Business Transformation - Hamkalo, O. B.; Demkiv, Kh. S. (Statistics of Ukraine, 2023)
The article considers theoretical and applied aspects of applying digital innovations in the system of organization and conducting management analysis of enterprise activities. The content of the concepts of digital innovations and business transformation in the system of management analysis is disclosed. The role of management analysis in the context of business transformation is determined. The main digital innovations that affect modern business and contribute to the effective management of an enterprise are considered. The study analyzes the use of digital innovations in the preparation and implementation of management decisions, formulates and discloses recommendations for their implementation in order to improve the efficiency of enterprise activities in the field of strategic planning, operational analysis and risk management. Examples of digital innovations for implementation in the enterprise management system for analysis, evaluation and strategic planning of its activities are provided. The main aspects of the use of digital innovations for management analysis are revealed. The challenges and difficulties associated with the introduction of digital innovations in the process of management analysis are analyzed, indicating possible impacts on the organizational structure, decision-making processes and strategic planning. Possible ways to overcome these obstacles are considered. It is determined how digital innovations change the approach to data collection, processing and analysis in the process of management analysis and allow obtaining more accurate and comprehensive data for decision-making. The article also examines the role of management analysis based on digital data in making informed decisions and developing optimal strategies for enterprise development and the ability to assess various scenarios, identify business strengths and weaknesses. The author also considers technological and analytical tools that support the effectiveness of management analysis in the context of digital innovations and affect the quality of enterprise performance. It is substantiated that digital technologies and data analysis are key factors in the successful transformation of enterprises to meet modern requirements. They help to improve the efficiency of business processes, identify new opportunities and provide competitive advantages in the market by changing the approach to business management and the way an enterprise interacts with its customers.